Assessing Attitude and Practice on Study Habits among Higher Secondary Students - Mondal, Gargi; Samaddar, Ritu; Sikdar, Deb Prasad (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Study habits play an important role in the life of students those students who have good study have been found to have higher success rate. The main aim of the research was to verify the attitude of student towards study habit and the extent of their real-life application i.e. practice in view of the attitude. The study investigates the study habits of senior secondary school students in Bardhaman district, West Bengal, India using a descriptive-survey method. A stratified random sampling technique was employed to select 637 students, using Attitude and practice tool of Mondal and Samaddar's (2024) regarding study habits for data collection. In the finding. The study reveals significant differences in attitudes and practices towards study habits based on factors like gender, location, and education stream, with a positive correlation between attitudes and practice, contributing to our understanding of study habits' significance. In the study positive relationship between attitude and practice is observed which is (0.754) highly corelated.